Rules of evidence - Nussberger, Clint J (Marine Corps Gazette, 2006)
Examines the issues of evidence collection and the interaction between probable cause and target selection in the context of irregular warfare where insurgents are detained rather than interned and subject to prosecution. For United States Marine Corps counterinsurgency operations in Iraq, thorough intelligence and evidence preparation is critical.